Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Kubus dan Balok - Selfiani, Selfiani; Machmud, Tedy; Resmawan, Resmawan; Ismail, Yamin (Scimadly Publishing, 2022)
This study discusses the effect of the Problem Based Learning model on students' mathematical creative thinking skills on cube and cuboid material. The research was carried out using an experimental method involving students of SMP Negeri 3 Limboto Barat as research subjects. The research design used is Post Test Only Control Design. Sampling was carried out using the Simple Random Sampling technique. Measuring mathematical creative thinking ability is done using a test instrument that has met the requirements of item validity and instrument reliability requirements. The results showed that applying the Problem-Based Learning model in learning significantly influenced students' creative thinking skills on cube and cuboid material. This can be seen from students' mathematical creative thinking ability in learning using the Problem-Based Learning model, which is higher than students' mathematical creative thinking ability in direct learning.